The prevalence and risk factors of sarcopenia in rheumatoid arthritis patients: A systematic review and meta-regression analysis - Li, Tzu-Hao; Chang, Yu-Sheng; Liu, Chih-Wei; Su, Chin-Fang; Tsai, Hung-Cheng; Tsao, Yen-Po; Liao, Hsien-Tzung; Chen, Ming-Han; Chuang, Chih-Cheng; Yang, Ying-Ying; Tsai, Chang-Youh (Seminars in arthritis and rheumatism, 2021)
•The estimated prevalence of sarcopenia in RA was 31%, without significant differences between various living area and diagnostic modalities.•Disease duration, DAS28 and HAQ were predictors of sarcopenia development in patients with RA.•Functional limitation, CRP and RF seropositivity were identified as additional risk factors. Sarcopenia is an ever-increasingly recognized entity in aging or chronically-ill individuals. A recent surge of researches came out on sarcopenia in rheumatoid arthritis (RA). However, the results varied widely. We tried to assess the prevalence of and associated factors with sarcopenia in patients with RA. We searched the investigations dealing with the prevalence of and associated factors with sarcopenia in RA from PubMed, EMBASE, CENTRAL, EBSCOhost, Airiti Library, CEPS, CNKI and J-STAGE from the inception to January 11, 2020. Effects regarding prevalence and associated factors were extracted and evaluated by random-effects model. Sensitivity analysis was also performed. Seventeen studies containing 3,140 RA subjects were identified. After exclusion of outliers, the pooled prevalence of sarcopenia was 31%. Neither ongoing-study districts nor diagnostic modalities affected prevalence significantly. Any associated factors being mentioned in at least two publications were analyzed, yielding functional limitation (Steinbrocker stage III/IV), high CRP and RF seropositivity as the significant risk factors. Based on disease durations, we carried out meta-regression and found DAS28 and HAQ are predictive models. There was no alteration in the interpretation of results from sensitivity analysis after removal of any studies skewed in sampling distribution. The prevalence of sarcopenia in patients with RA is high, compared to that in general counterparts. Disease duration rather than age, residing area or diagnostic modalities influences sarcopenia development; DAS28 and HAQ predict occurrence. High index of suspicion to facilitate early detection of sarcopenia in RA patients is important.